Efficacy and safety of nano-silver dressings combined with recombinant human epidermal growth factor for deep second-degree burns: A meta-analysis. Issue 3 (May 2021) - Li, Siqing; Liu, Yuan; Huang, Zehao; Kou, Yan; Hu, Ailing
Highlights: What is already known about the topic? Experts advise reduce the use of silver sulphadiazine paste in treatment of deep second-degree burns. This comprehensive meta-analysis of the available evidence suggests that the use of nano-silver dressings combined with recombinant human epidermal growth factor results in a shorter duration of wound healing, reduced wound bacteria positive rates and adverse reaction rates, and improved wound healing rates. The therapeutic effect of nano-silver dressing combined with recombinant human epidermal growth factor on deep second-degree burns needs to be further improved. More high-quality research is needed to determine the risks of nano-silver dressing combined with recombinant human epidermal growth factor for deep second-degree burns. What this paper adds There is no strong evidence to suggest for or against the ues of nano-silver dressings combined with recombinant human epidermal growth factor for deep second-degree burns. More high-quality research is needed to determine the risks of nano-silver dressings combined with recombinant human epidermal growth factor for deep second-degree burns. Abstract: Objective: The purpose of this meta-analysis was to assess the efficacy and safety of nano-silver dressing combined with recombinant human epidermal growth factor for deep second-degree burns. Methods: PubMed, Web of Science, EMBASE, Cochrane Library and other databases were searched to identify relevant randomised controlled trials. Results: Twelve studies that assessed nano-silver dressing combined with recombinant human epidermal growth factor were identified. Nano-silver dressing combined with recombinant human epidermal growth factor for deep second-degree burns could significantly reduce the duration of wound healing (mean difference −5.68, 95% CI −7.38 – −3.99, P < 0.00001), the wound healing rate (risk ratio [RR] 0.34, 95% CI 0.23–0.48, P < 0.00001), the rate of scar hyperplasia (RR 0.67, 95% CI 0.54–0.84, P = 0.0004), the wound bacterial positive rate (RR 0.50, 95% CI 0.28–0.89, P = 0.02), and the adverse reactions rate (RR 0.31, 95% CI 0.16–0.58, P = 0.0003). Conclusion: This comprehensive meta-analysis of the available evidence suggest that the use of nano-silver dressing combined with recombinant human epidermal growth factor results in shorter duration of wound healing, reduced wound bacterial positive rates and adverse reactions rate, and improved wound healing rates.